Evaluation of Liver Fibrosis through Noninvasive Tests in Steatotic Liver Disease - Yuri Cho (The Korean Journal of Gastroenterology)
Liver fibrosis, a critical predictor of the prognosis of metabolic dysfunction-associated steatotic liver disease (MASLD), is traditionally diagnosed via biopsy. Nevertheless, non-invasive alternatives, such as serum biomarkers, vibration-controlled transient elastography, and magnetic resonance elastography, have become prominent because of the limitations of biopsies. Serum biomarkers, such as fibrosis-4 index and NFS Score, are also used widely, offering reliable diagnostic performance for advanced fibrosis. Vibration-controlled transient elastography and shear wave elastography provide further non-invasive evaluations with high diagnostic accuracy, particularly for advanced fibrosis, but the results may be affected by factors such as obesity. Magnetic resonance elastography, with superior diagnostic accuracy and operator independence, is a promising method, but its high cost and limited availability restrict its widespread use. Emerging algorithms, such as NIS4, FAST, or MAST score, have strong potential in identifying high-risk metabolic dysfunction-associated steatohepatitis patients. The integration of multiple non-invasive methods can optimize diagnostic accuracy, reducing the need for invasive biopsies while identifying patients at risk of liver-related complications. Further research is needed to refine these diagnostic tools and improve accessibility.